2018
DOI: 10.15171/ijer.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Nurses and Related Factors

Abstract: Background and aims:A high number of healthcare team members are nurses. Nurses' quality of life level is an important issue because it affects their level of care delivered to their patients. Knowledge about nurses' level of quality of life is useful for planning. The present study was conducted to examine the quality of life of nurses and related factors. Methods: This cross-sectional descriptive study was performed during 2015-2016. Samples were recruited from single nurses who worked in teaching hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Overall, LPNs in this study (mean age: 40) rated their health as being lower than Canadian norms for people 35–44 [ 23 ] across every SF-36 subscale. However, this sample reported higher mean scores than some published examples of nurses’ SF-36 scores [ 6 , 11 , 42 ], and similar scores to those of Omrani and Talebi [ 36 ]. These results indicate that LPNs report their health as lower than the general population, but higher than other groups of nurses.…”
Section: Discussionsupporting
confidence: 52%
“…Overall, LPNs in this study (mean age: 40) rated their health as being lower than Canadian norms for people 35–44 [ 23 ] across every SF-36 subscale. However, this sample reported higher mean scores than some published examples of nurses’ SF-36 scores [ 6 , 11 , 42 ], and similar scores to those of Omrani and Talebi [ 36 ]. These results indicate that LPNs report their health as lower than the general population, but higher than other groups of nurses.…”
Section: Discussionsupporting
confidence: 52%
“…Moradi et al 18 reported a similar finding in the study completed in Iran. However, there are research studies 16,19,21,22 in the literature that showed a significant association between abovementioned demographic variables with physical health.…”
Section: Discussionmentioning
confidence: 96%
“…These findings were in contrast with the study completed in Brazil 2010 24 and the study conducted in Iran 2018. 25…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also showed that social functioning had the highest value and that nurses' gender significantly influenced their quality of life (p<0.05). 18 Nurses who work in hospitals confront various Acknowledging the significant harm that workrelated stress can have on physical and mental well-being and its potential to reduce productivity and cause economic instability is essential.…”
Section: Discussionmentioning
confidence: 99%